Satisfaction with life during the COVID-19 pandemic: the role of affect balance and self-concept clarity - Qing Erh Sow; Kususanto Ditto Prihadi; Ida Kusnawati Tjahjani (Intelektual Pustaka Media Utama, 2022)
As one significant indicator of mental wellbeing, satisfaction with life plays important roles in the society and among individuals. Nevertheless, studies have stated that the formation of life satisfaction was different between before and during the pandemic. Among most people, the differences were caused by the implication of social distancing protocols, where people were not fully connected to one another without the help of electronic media; therefore, some of their social roles were altered or became less meaningful. Such changes affected the clarity of how individuals see themselves, as well as the balance of their negative and positive emotional experiences (affect balance). We hypothesized that self-concept clarity predicts life satisfaction through affect balance. We collected our data from 139 Malaysian adults aged between 18 to 60 years through various social media platforms to complete the self-concept clarity scale (SCCS), satisfaction with life scale (SWLS), and scale of positive and negative experience (SPANE). Results of the bootstrap analysis with a 95% confidence interval indicated that the affect balance partially mediated the relationship between self-concept clarity and life satisfaction.